Controlling nanoparticle crystallinity and surface enrichment in polymer (P3HT)/Nanoparticle(PCBM) blend films with tunable soft confinement. (31st January 2018) - Huq, Abul F.; Zvonkina, Irina; Al-Enizi, Abdullah M.; Karim, Alamgir
Abstract: Light absorbing semi-crystalline polymers are often blended with crystallizing conductive nanoparticles for enhanced electrical properties in thin film photovoltaics. Here we develop a general strategy to control nanoparticles degree of crystallinity and relative surface segregation at the air boundary, important for flexible organic electronics. While SAM modified silicon surface has been extensively studied to control substrate segregation in OPV blend films, controlling the same at the air surface has not been explored significantly. Semi-crystalline polymers have high surface energy much like nanoparticles, so that the surface energy differential can be low, allowing for tunability of the lower surface energy component by a soft confinement strategy. Soft confinement can also be used to control the degree of crystallization of the surface segregating component. To this end, we study effect of soft confinement on P3HT:PCBM blend films, a model semi-crystalline polymer/nanoparticle system, in which both components crystallize with P3HT migrating to free air surface. We present a novel UVO treated fluorosilicone elastomer transient capping layer with controlled surface energy, γ, that can induce PCBM migration to the elastomer capped blend film interface. The transition of P3HT crystalline structure from face-on to edge-on with annealing is largely unaffected in the process. Effects of the casting solvent on the crystallization kinetics of thin P3HT:PCBM blend films under wide range of fluoroelastomer surface energy values γ (29–70 mJ/m 2 ) was explored with differing outcomes. A notable result is that PCBM crystallization cast from o-dichlorobenzene (DCB) is suppressed without diffusing into the fluorosilicone layer. Our tunable surface energy soft-confinement strategy should be extendable to other polymer/nanoparticle thin film systems for broader impact in the scientific community. Graphical abstract: Highlights: PCBM nanoparticles distribution in P3HT polymer BHJ blend films. Suppression of PCBM crystallization with soft confinement. Surface energy controlled fluoropolymer confinement. Process and design strategy for polymer solar cell.